Homoconjugation in poly(phenylene methylene)s: A case study of non‐π‐conjugated polymers with unexpected fluorescent properties. Issue 9 (24th January 2017) - Braendle, Andreas; Perevedentsev, Aleksandr; Cheetham, Nathan J.; Stavrinou, Paul N.; Schachner, Jörg A.; Mösch‐Zanetti, Nadia C.; Niederberger, Markus; Caseri, Walter R.
ABSTRACT: Poly(phenylene methylene) (PPM) exhibits pronounced blue fluorescence in solutions as well as in the solid state despite its non‐π‐conjugated nature. Optical spectroscopy was used to explore the characteristics and the physical origin of its unexpected optical properties, namely absorption in the 350–450 nm and photoluminescence in the 400–600 nm spectral regions. It is shown that PPM possesses two discrete optically active species, and a relatively long photoluminescence lifetime (>8 ns) in the solid‐state. Given the evidence reported herein, π‐stacking and aggregation/crystallization, as well as the formation of anthracene‐related impurities, are excluded as the probable origins of the optical properties. Instead there is sufficient evidence that PPM supports homoconjugation, that is: π‐orbital overlap across adjacent repeat units enabled by particular chain conformation(s), which is confirmed by DFT calculations. Furthermore, poly(2‐methylphenylene methylene) and poly(2, 4, 6‐trimethylphenylene methylene) – two derivatives of PPM – were synthesized and found to exhibit comparable spectroscopic properties, confirming the generality of the findings reported for PPM. Cyclic voltammetry measurements revealed the HOMO–LUMO gap to be 3.2–3.3 eV for all three polymers. This study illustrates a new approach to the design of light‐emitting polymers possessing hitherto unknown optical properties. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 707–720 Abstract : The occurrence of homoconjugation is demonstrated for poly(phenylene methylene) which – despite featuring aromatic rings separated by an insulating methylene group – exhibits pronounced blue fluorescence in solutions and solid‐state. Notably, it features an extremely long solid‐state photoluminescence lifetime (>8 ns). This first demonstration of fluorescent properties in macromolecules enabled by homoconjugation along the backbone opens new strategies for the design of next‐generation light‐emitting polymers.